On the connection between first integrals, integral invariants and potentiality of evolutionary equations - Savchin, Vladimir; Budochkina, Svetlana; Gondo, Yake; Slavko, Aleksandra (Eurasian Mathematical Journal, 2018)
Using methods of nonlinear analysis, we have established the connection between first integrals and absolute integral invariants of some evolutionary equations similarly to the case of dynamics of finite dimensional systems.